Analysis of Surgical Outcomes and Determinants of Litigation Among Women With Transvaginal Mesh Complications. Issue 6 (November 2016) - Zoorob, Dani; Karram, Mickey; Stecher, Anna; Maxwell, Rose; Whiteside, James
Abstract : Objectives: To identify litigation predictors among women with complications of transvaginal mesh. Methods: Chart review and patient survey were conducted among women who had undergone a complication-related explant of a transvaginal prolapse or incontinence sling mesh. Trained study personnel administered a 57-question survey addressing subjective complaints related to bowel, bladder, sexual dysfunction, and development of pain or recurrent prolapse. These data were analyzed with respect to the subject's reported pursuit of litigation related to the mesh complication. Categorical and continuous variables were analyzed using the χ 2 test and the t test as indicated. Results: Ninety-five (68%) of 139 women completed the surveys with 60% of the patients pursuing litigation at the time of the survey. Individual risk factors for pursuing litigation included development of vaginal pain after mesh placement ( P = 0.01); dyspareunia after mesh placement ( P = 0.01); persistence of dyspareunia, suprapubic pain, and groin pain after mesh excision ( P = 0.04, P = 0.02, and P = 0.001, respectively); unsuccessful attempts at conservative management of pelvic pain using pelvic floor rehabilitation ( P = 0.002). Conclusion: There is an association between a higher likelihood of pursuing litigation and new-onset or persistent pain symptoms attributable to transvaginal mesh. Abstract : Patients with new-onset or persistent pain symptoms attributable to transvaginal mesh appear to be more commonly involved in litigation.